Zavajajoče dojemanje in gospodarska učinkovitost regionalnega sistema - Malul, Miki (Urbani izziv, 2012)
This paper's innovation is the introduction of a misperception effect to the core-periphery model. Using a theoretical model, we show that the free market will lead to distorted spatial distribution of firms between the core and the periphery when a misperception effect is introduced into the model. Based on aquestionnaire, we found that a misperception regarding the quality of the production factor exists in favour of the core compared to the periphery. This misperception is found not only in the eyes of the core with regard to the periphery, but also in the periphery regarding itself. We suggest marketing and empowerment of the periphery as a policy tool to alter these misperceptions.
Keywords: efficiency; lokacija; poslovna uspešnost; poslovne cone; proizvodnja; učinkovitost